2019
DOI: 10.1080/00313831.2019.1595715
|View full text |Cite
|
Sign up to set email alerts
|

Optometric Disorders in Children and Adults with Dyslexia

Abstract: Optometric disorders are likely to increase the difficulties experienced by an individual who is struggling to read. There are some reports of a higher incidence of visual abnormalities in children with dyslexia, but there has been little investigation into adults. We therefore investigated the optometric status of a population comprising children and adults with dyslexia. Fifty-four patients (27 with dyslexia, 27 controls) underwent extensive optometric testing. Measurements included visual acuity, cycloplegi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 38 publications
5
13
0
Order By: Relevance
“…Only one child was myopic. This is in line with other Nordic studies in children and adolescents [46][47][48]84 . Although most children had good binocular vision, the children in the pain group had a significantly reduced AC/A compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Only one child was myopic. This is in line with other Nordic studies in children and adolescents [46][47][48]84 . Although most children had good binocular vision, the children in the pain group had a significantly reduced AC/A compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The eye and physical examination revealed that headaches and trigger points were also common in the control group, however, these children had not been in contact with health care personnel. Further, the results showed associations between symptoms and need for new glasses in 40% of the control group, in line with previous studies showing that 10-40% of school children need glasses to obtain satisfactory vision 30,[46][47][48] . That the eye examination also revealed symptoms in the control group, supports that children often are unaware of symptoms of uncorrected vision problems.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The relationship between accommodation, visual acuity and fixation stability have been investigated previously (Evans et al, 1994;Vikesdal et al, 2020;Wahlberg-Ramsay et al, 2012;Ygge et al, 1993). Some individuals with dyslexia exhibit a reduction in acuity compared to controls, and lower levels of accommodation amplitude has been reported (Evans et al, 1994;Vikesdal et al, 2020;Wahlberg-Ramsay et al, 2012;Ygge et al, 1993).…”
Section: Introductionmentioning
confidence: 99%